Assessment of IL‐18 Serum Level and Its Promoter Polymorphisms in the Saudi Coronary Artery Disease (CAD) Patients. Issue 7 (16th February 2017) - Jabir, Nasimudeen R.; Firoz, Chelapram K.; Kamal, Mohammad A.; Damanhouri, Ghazi A.; Alama, Mohammed Nabil; Alam, Qamre; Haque, Absarul; Almehdar, Hussein A.; Tabrez, Shams
ABSTRACT: The purpose of the current study was to find out the possible changes polymorphic site at the promoter region of IL‐18 gene in Saudi CAD patients. We have also measured serum IL‐18 level to find out, the likely association between its level and polymorphic site. The present study included total 197 subjects (98 confirmed CAD patients both men and women and 99 healthy control individuals). Serum concentration of IL‐18 was measured by enzyme linked immuno‐sorbent assay. For SNPs analysis, sanger method of DNA sequencing was followed. We observed variable numbers of SNPs at −137 C/G, −607 A/C, and −656 T/G promoter sites in our studied samples. However, the observed changes in the number of SNP hotspots were found to be non‐significant compared with control. IL‐18 level was found to be significantly ( P < 0.001) elevated in CAD patients compared with control individuals. The highest rise of around 36% ( P < 0.001) in IL‐18 level was recorded in unstable angina (UA) patients. Moreover, the group belonging to UA and non‐ST segment elevation myocardial infarction (NSTEMI) showed only 6% rise. On the basis of our result, inflammation seems to have a role in the pathogenesis of CAD but not leading to the significant changes at the genetic level. J. Cell. Biochem. 118: 1849–1854, 2017. © 2017 Wiley Periodicals, Inc. Abstract : In this article, we observed non‐significant changes in the IL‐18 SNP hotspots. However, the serum IL‐18 level was found to be significantly elevated in CAD patients. The highest rise of around 36% was recorded in unstable angina (UA) patients.